THE AFFECT OF WORK DISCIPLINE AND COMPETENCE ON EMPLOYEE PERFORMANCE (CASE STUDY AT BALAI KESEHATAN MATA MASYARAKAT SULAWESI UTARA) - Noel, Flavia Reva; Lapian, S.L.H.V.Joyce; Pandowo, Merinda (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2017)
Abstract: Human resource management as a strategic approach to the management of human resources that involves all management decisions and actions that affect the relationship between the organization and employees. Human are the most important resource in an organization’s business success and to support organization’s work. To improve the employee performance in an organization, they should enforce discipline of the employees and competence. This research aimed to analyzed The Affect of Employee Work Discipline and Competence on Employee Performance in Balai Kesehatan Mata Masyarakat Sulawesi Utara. This research was analyzed by using multiple regression analysis. Data collected through questionnaire distribute to 55 respondents and the data was taken by simple random sampling. This research showed that Employee Work Discipline and Competence simultaneously influence Employee Performance, Work Discipline has significant influence on Employee Performance partially and Competence has no significant influence on Employee Performance partially. It is expected the company to pay attention about work discipline in term by supporting the achievement of organization’s work.                                                  Keywords: work discipline,competence, employee performance.